THE ROLE AND IMPORTANCE OF THE CAPITAL MARKET IN THE NATIONAL AND WORLD ECONOMY - Saydaliev Saydimaqsudxoja Saydaxmadovich (Scholar Express Journals, 2021)
In this article the role and importance of the capital market in the national and global economy is discussed. Also, taking into account the development trends of the capital market, the main features of the capital market are identified by the author's scientifically based views.
Keywords: investor; deposit; bond; World Bank